Equality of Opportunity for Well-Being - Daniel Gerszon Mahler; Xavier Ramos (Institute of Labor Economics (IZA), 2017)
A growing literature has tried to measure the extent to which individuals have equal opportunities to acquire income. At the same time, policy makers have doubled down on efforts to go beyond income when measuring well-being. We attempt to bridge these two areas by measuring the extent to which individuals have equal opportunities to achieve a high level of well-being. We use the German Socio-Economic Panel to measure well-being in four different ways including incomes. This makes it possible to determine if the way well-being is measured matters for identifying who the opportunity-deprived are and for tracking inequality of opportunity over time. We find that, regardless of how well-being is measured, the same people are opportunity-deprived and equality of opportunity has improved over the past 20 years. This suggests that going beyond income has little relevance if the objective is to provide equal opportunities.
Keywords: D3; D63; I31; 330; responsibility; measurement; equality of opportunity; effort; well-being